The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2013
DOI: 10.1590/0102-311x00175912
|View full text |Cite
|
Sign up to set email alerts
|

Distância percebida até as instalações de lazer e sua associação com a prática de atividade física e de exercícios em adolescentes de Curitiba, Paraná, Brasil

Abstract: The aim of this study was to verify the association between perceived distance to recreational facilities (parks, gyms, sports courts, and bike lanes) for physical activity and exercise among adolescents in Curitiba, Paraná State, Brazil. A cross-sectional study was conducted with a representative sample of 1,474 adolescents (14-18 years) enrolled in public schools. There was an inverse association between distance (> 31 minutes) to gyms and sports courts and physical activity among boys (PR = 0.78; 95%CI: 0.6… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
2
0
4

Year Published

2014
2014
2020
2020

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(8 citation statements)
references
References 42 publications
2
2
0
4
Order By: Relevance
“…Factors associated with physical activity are broadly debatable, given that the results from different studies are contradictory. Those found in the present study corroborate several studies that have demonstrated a positive association between physical activity and male gender,7 , 9 , 10 , 13 paternal education,8 , 24 perception of physical activity,25 availability of places for physical activity practice,6 , 26 participation in physical education classes,7 - 9 and sedentary behavior 911 , 13 …”
Section: Discussionsupporting
confidence: 92%
See 4 more Smart Citations
“…Factors associated with physical activity are broadly debatable, given that the results from different studies are contradictory. Those found in the present study corroborate several studies that have demonstrated a positive association between physical activity and male gender,7 , 9 , 10 , 13 paternal education,8 , 24 perception of physical activity,25 availability of places for physical activity practice,6 , 26 participation in physical education classes,7 - 9 and sedentary behavior 911 , 13 …”
Section: Discussionsupporting
confidence: 92%
“…The results are within the range observed in other studies that used 300 minutes as the cutoff point (14.5% to 50%),6 - 12 but lower than those found when the cutoff point used was 420 minutes, which ranged from 15 to 49.5% 1315 , 18 …”
Section: Discussionsupporting
confidence: 85%
See 3 more Smart Citations